2017
DOI: 10.1002/2016gc006644
|View full text |Cite
|
Sign up to set email alerts
|

Trade winds drive pronounced seasonality in carbonate chemistry in a tropical Western Pacific island cave—Implications for speleothem paleoclimatology

Abstract: Carbon dioxide concentrations in caves are a primary driver of rates of carbonate dissolution and precipitation, exerting strong control on speleothem growth rate and geochemistry. Long-term cave monitoring studies in midlatitude caves have observed seasonal variability in cave pCO 2, whereby airflow is driven by temperature contrasts between the surface and subsurface. In tropical settings, where diurnal temperature cycles are larger than seasonal temperature cycles, it has been proposed that caves will venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 80 publications
(99 reference statements)
0
19
0
Order By: Relevance
“…On shorter timescales, we note that the periods of lower δ 13 C CO2 were observed in June 2012, December 2012, November 2013, and April 2014. Such periods of decreased ventilation could be driven by variations in soil δ 13 C CO2 value, temperature, and wind direction (James et al, ; Noronha et al, ). Studies have also shown that seasonally, ventilation can be impacted by the temperature difference between the cave and the outside.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On shorter timescales, we note that the periods of lower δ 13 C CO2 were observed in June 2012, December 2012, November 2013, and April 2014. Such periods of decreased ventilation could be driven by variations in soil δ 13 C CO2 value, temperature, and wind direction (James et al, ; Noronha et al, ). Studies have also shown that seasonally, ventilation can be impacted by the temperature difference between the cave and the outside.…”
Section: Discussionmentioning
confidence: 99%
“…Within the cave, atmospheric CO 2 ventilation may drive variations in the δ 13 C values of the CO 2 and degassing processes can affect the δ 13 C values of the speleothem calcite similar to oxygen isotopes (Bergel et al, ; Meyer et al, ). Monitoring studies show that cave ventilation can vary seasonally (Mattey et al, , ; Noronha et al, ; Vieten et al, ).…”
Section: Stalagmite Geochemistrymentioning
confidence: 99%
“…Our results indicate that changes in atmosphere barometric pressure determine the advective airflow direction. This is presumably due to the difference between the barometric pressure and the cavity pressure caused by the vertical propagation of the barometric pressure Neeper and Stauffer, 2012;Perina, 2014;You et al, 2011). In the case of positive barometric pressure changes (i.e., increase in barometric pressure over time), the barometric pressure will be greater than the cavity pressure and thus inflow of air will develop.…”
Section: Shaft Geometrymentioning
confidence: 99%
“…Understanding air transport between the Earth's subsurface and the atmosphere is a key element in the study of surface and near-surface biological, chemical, and physical processes. Air transport between the Earth and the atmosphere is commonly driven by diffusive and advective mechanisms (Choi and Smith, 2005;Ganot et al, 2014;Hillel, 1998;Kawamoto et al, 2006;Kuang et al, 2013;Noronha et al, 2017;Sánchez-Cañete et al, 2013) and has mainly been studied within soils (e.g., Allaire et al, 2009;Bayer et al, 2017;Choi and Smith, 2005;Zeng et al, 2017). However, as different types of natural or artificial boreholes and shafts also exist (e.g., Berthold and Börner, 2008;Kang et al, 2014Kang et al, , 2015, understanding the mechanisms that govern air and green-house gas (GHG) transport in such conduits is also important (Berthold and Börner, 2008;Perrier et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation